"A day-to-day struggle": A comparative qualitative study on experiences of women with endometriosis and chronic pelvic pain. (November 2022) - Hawkey, Alexandra; Chalmers, K. Jane; Micheal, Sowbhagya; Diezel, Helene; Armour, Mike
Chronic pelvic pain (CPP) in women is a term that encompasses a range of conditions, including endometriosis, vulvodynia, painful bladder syndrome and adenomyosis. Given the impact on penetrative sex, fertility and potentially motherhood, CPP may also impact on women's identities as a wife or partner, a mother, and a woman. The aim of this study was to explore similarities and differences in experiences of women with endometriosis and non-endometriosis related CPP. A total of 17 participants aged between 21 and 48 years old participated in three focus groups. Using reflexive thematic analysis three main themes were found: the struggling woman, the unheard woman and the self-silenced woman. Women, regardless of the cause of their CPP, reported significant impacts on their intimate relationships, fertility, and parenting but those with non-endometriosis CPP often reported greater trouble communicating about pelvic pain in the workplace due to the "taboo" nature of discussing their vulval pain. Many participants described how a societal normalisation of pelvic pain resulted in women silencing their experiences, rendering their pain invisible. While women wanted to resist such silencing through information and support seeking, women with non-endometriosis CPP described fewer avenues to accessing credible informational resources or networks for support.